Sox-4, an Sry-like HMG box protein, is a transcriptional activator in lymphocytes. - van de Wetering, M (1993)
Previous studies in lymphocytes have described two DNA-binding HMG box proteins, TCF-1 and LEF-1, with affinity for the A/TA/TCAAAG motif found in several T cell-specific enhancers. Evaluation of cotransfection experiments in non-T cells and the observed inactivity of an AACAAAG concatamer in the TCF-1/LEF-1-expressing T cell line BW5147, led us to conclude that these two proteins did not mediate the observed enhancer effect. We therefore searched for additional HMG box proteins. By a PCR-aided strategy, we cloned Sox-4, a gene with homology to the HMG box region of the sex determining gene SRY. Sox-4 was expressed in T and pre-B lymphocyte lines and in the murine thymus. Significantly, BW5147 T cells did not express Sox-4. Recombinant Sox-4 bound with high affinity (Kd 3 x 10(-11) M) to the minor groove of the AACAAAG motif, most likely contacting all seven base pairs. In contrast with observations on TCF-1 and LEF-1, cotransfection with Sox-4 unveiled a transactivating capacity, which mapped to its serine-rich C terminus. This region remained functional upon grafting onto a GAL4 DNA-binding domain. Sox-4 is thus the first 'classical' transcription factor in the Sox gene family with separable DNA-binding and transactivation domains. Our observations indicate that a detailed understanding of T cell-specific gene control must integrate the concerted activity of at least three tissue-specific HMG box genes.